Pain threshold - measure of pain sensitivity or social behavior? - Modić Stanke, Koraljka (Array, 2014)
The main objective of this study was to examine the role of social status of the experimenter on the pain threshold for mechanical pressure. In addition, the aim was to examine the possible interaction of participant’s gender and status of experimenter on pain threshold. Ninety-six first-year undergraduate psychology students participated in the study. They have been randomly assigned into two groups, but with the restriction that in both groups was equal number of male participants. In one group pain threshold was measured by their professor, and in another group by a third year undergraduate student. Pain threshold to mechanical pressure was measured at four locations - the index finger and little finger on the left and right hand, respectively. Neither participants nor the two experimenters were aware of the research hypotheses. Both experimenters were equally trained to measure pain threshold by algometer device. Participants received description of pain threshold and a clear instruction that in this study goal is measurement of pain threshold, not pain tolerance. Obtained results showed statistically significant and large difference in pain threshold with regard to experimenter status. When the experimenter was professor, pain threshold was higher. Also, results confirmed expected role of participants' gender meaning that male participants had higher pain threshold. Interaction of experimenter status and participant’s gender was also statistically significant. Pain threshold was higher in both genders when the experimenter was a professor, but difference was greater in male students. Results of this study are consistent with previous studies that demonstrated effect of experimenter status on pain tolerance and pain unpleasantness, measures generally demonstrated to be more subject to changes in measurement context. To conclude, the results of this study show that the effect of experimenter status is very large (partial eta = .59), suggesting that obtained differences are primarily caused by social behavior rather than changes in sensitivity to painful stimulation. Therefore, pain threshold does not seem to be context irrelevant measure, which is something that should be considered in further pain studies.